2017
DOI: 10.3892/etm.2017.4258
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PKCα reduces the ability of migration of kidney cancer cells but has no impact on cell apoptosis

Abstract: Abstract. Kidney cancer is among the most important causes of cancer-associated mortality worldwide. The present study aimed to evaluate protein kinase C α (PKCα) expression in kidney cancer tissues and cell lines, and its significance in apoptosis and migration. Expression of PKCα was analyzed using quantitative polymerase chain reaction and western blotting. In addition, the inhibitor of PKCα (calphostin C and GO6976) was used to treat kidney cancer cells. The ACHN cell line was generated with PKCα-small-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…PKCα is involved in the proliferation, migration, invasion, and apoptosis, signal transducers and activators of PKCα are constitutively activated in many human solid tumors including breast cancer, and inhibition of PKCα was consider as a novel strategy in developing anticancer agents development, cellular proliferation, and migration . In the present study, we demonstrated the ability of miR‐216a to activate apoptosis through the regulation of PKCα in breast cancer cells.…”
Section: Discussionsupporting
confidence: 49%
“…PKCα is involved in the proliferation, migration, invasion, and apoptosis, signal transducers and activators of PKCα are constitutively activated in many human solid tumors including breast cancer, and inhibition of PKCα was consider as a novel strategy in developing anticancer agents development, cellular proliferation, and migration . In the present study, we demonstrated the ability of miR‐216a to activate apoptosis through the regulation of PKCα in breast cancer cells.…”
Section: Discussionsupporting
confidence: 49%
“…While Harazono and colleagues demonstrated that MCP suppressed Gal:Bax heterodimerization and promoted apoptosis 63, Li and co-workers showed that MCP attenuated CDDP-induced AKI by suppressing protein kinase C-α (PKC-α)-driven apoptosis 25. These opposite findings may be explained by the fact that MCP, in similar manner as PKC-α, interferes with multiple intracellular pathways and, therefore, could acts as pro- or anti-apoptotic agent, depending upon cell type or tissue microenvironment 65-68. Furthermore, different effects of Gal-3 inhibition in modulation of CDDP-induced apoptosis could be due to the different doses of CDDP (16mg/kg vs. 20mgkg body weight) which were used in our and in study conducted by Li and colleagues 25.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation initiates c-Abl/PKCδ/Rac1/p38 cascades and leads to the oligomerization of Bax and Bak, which results in the release of cytochrome C [ 48 ]. It has been demonstrated that PKCα might not contribute to the progression of kidney carcinoma since its inhibition does not affect kidney cancer cell apoptosis [ 49 ]. Additionally, in some reports, PKC activation by oxidative stress and irradiation is not always accompanied by translocation [ 50 ].…”
Section: Pkcs In Cancermentioning
confidence: 99%